Work–family balance in the construction industry: why gender analysis matters to develop sustainable interventions. Issue 11 (2nd November 2022) - Lefrançois, Mélanie; Trottier, Mélanie
Abstract: Work–family balance (WFB) in the construction sector has rarely been studied. Hardship, atypical schedules and seasonal work create challenging conditions for parents in this male-dominated industry. Semi-structured interviews with workers (14 men, 6 women) and a survey of 789 on-site workers (85% men, 15% women) were conducted as part of a wider participatory action-research project involving governmental actors. Triangulation of the interview and survey data clarified the influence of quantitative and qualitative workload and of managerial support on work–family conflict. Results also show that male and female workers have differentiated experiences of WF issues and, consequently, develop different WF strategies while pursuing increased flexibility. The stereotyped conception of WF encourages social norms that have various impacts on mothers and fathers working in the industry. Recommendations for a cultural shift are proposed for employers in this industry, marked by a labour shortage and low retention of female workers. Practitioner summary: This paper provides a gendered analysis of work–family issues among on-site workers in the construction industry. It aims to inform ergonomists and occupational health researchers about the potential of inflexible work designs to convey stereotypes that can impact the sustainability and equity of workplace interventions.